Circe : [compact disc, unabridged] a novel - Miller, Madeline (Hachette Book Group, 2018)
In the house of Helios, mightiest of the Titans, a daughter is born. But Circe is a strange child-- not obviously powerful like her father, nor viciously alluring like her mother. Turning to the world of mortals for companionship, she discovers the power of witchcraft, which can transform rivals into monsters and menace the gods themselves. But to protect what she loves most, Circe must choose, once and for all, whether she belongs with the gods she is born from or the mortals she has come to love.